Exploring the Practice of “Dual-Teacher English Classroom” in Rural Small-Scale Schools — Taking a Township Primary School in Hengyang City as an Example - He, Wenjuan; Peng, Huimin; Lin, Yesheng (Pacific International Journal, 2026)
This study examined the application of the dual-teacher English classroom model in rural small-scale schools. Dual-teacher classroom, as an innovative educational model, combines online and offline teaching resources, which effectively made up for the shortcomings of insufficient teachers and resources in rural small-scale schools. The model was characterized by distinctive features, which not only enriched the teaching content and methods, but also stimulated students’ enthusiasm for learning through the collaborative teaching of urban and rural teachers. However, in practice, it also faces challenges such as insufficient teachers and lack of teacher-student communication. To cope with these problems, this study proposed targeted improvement strategies, such as optimizing the training system and creating opportunities for teacher-student dialogues, with a view to promote the better development of dual-teacher English classrooms in rural areas. Through this study, we firmly believe that the dual-teacher classroom model is of great significance in improving the quality of rural education and promoting the overall development of students, and is worthy of being widely promoted and applied.